Natural killer cell exhaustion in ovarian cancer: from molecular suppression to therapeutic revival - Ning, Jun; Yao, Lan (Frontiers in Immunology, 2026)
Ovarian cancer remains one of the most lethal gynecologic malignancies, largely due to its late-stage diagnosis and the establishment of an immunosuppressive tumor microenvironment (TME). Natural killer (NK) cells, key effectors of innate immunity, exhibit impaired cytotoxicity within this hostile niche. The dysfunction arises from multiple mechanisms, including suppression by immunosuppressive cytokines (TGF-β, MUC16), shedding of activating ligands (MICA/B, B7-H6, CD155), overexpression of inhibitory immune checkpoints (PD-1, TIGIT), and metabolic reprogramming shaped by glucose and lipid competition. Recent advances in NK cell–based immunotherapies—such as cytokine modulation, adoptive NK transfer, and checkpoint blockade—have demonstrated potential to reverse NK exhaustion and enhance antitumor efficacy. In this review, we systematically dissect the molecular and cellular pathways underlying NK cell suppression in ovarian cancer and evaluate emerging strategies to reinvigorate NK-mediated immunosurveillance.